Formulation and evaluation of multiparticulate drug delivery systems comprising telmisartan (Asian Journal of Pharmaceutics (AJP), 2015)
Telmisartan is poorly soluble in water, and the rate of dissolution, as well as bioavailability, is less. In the present study,an attempt has been made to improve the dissolution of the drug by coating the drug and carrier over sugar pellets.The solubility promoters such as alkalizes, binders and surfactants were selected to make the drug solution. The preparedÂ pellets were evaluated for their physicochemical properties and inâ€vitro dissolution. The drug release rate was found to beÂ more from the pellets coated with the coating solution containing the sodium hydroxide, Tween 80 and hydroxypropylÂ methylcellulose. The optimized pellet formulation was selected for stability study, and the inâ€vitro dissolution study showedÂ that was no difference in percent of drug released between initial and 6th month sample.Key words: Alkalizers, inâ€vitro dissolution, multiparticulate, telmisartan